Factors affecting teacher educators adoption of formative assessment strategies in the mathematics classroom - Justice Enu (Intelektual Pustaka Media Utama, 2021)
The purpose of this study was to look into the factors that influence mathematics teacher educators' formative assessment practices. This paper took a qualitative case study research design approach with six educators teaching mathematics in three teacher Colleges of Education in Ghana. The exploration focused on factors that hinders teacher educators use of formative assessment practices. Data were generated through the administration of semi – structured interviews and lesson observations. The qualitative data was analyzed using thematic analysis. Findings revealed that major factors which limit teacher educators formative assessment practices were: large class size, time, lack of transparency in assessment, and internal and external summative assessment issues. The factors limiting teacher educators' use of formative assessment (FA) discussed in this study are beneficial for teacher college administration in addressing the issues and educators in assisting pre-service teachers in eliminating these factors during their training and after passing out from the college of education to the teaching field. Based on the findings, it is recommended that a large scale study is conducted on factors that affect teachers formative assessment practices and the effect on students mathematics learning.